2000
DOI: 10.1093/humrep/15.12.2663
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and obstetric outcome after laparoscopic myomectomy of large myomata: a randomized comparison with abdominal myomectomy

Abstract: The purpose of this study was to compare, in infertile patients, the efficacy of laparoscopic myomectomy versus abdominal myomectomy, in restoring fertility and to evaluate the obstetric outcomes. Between January 1993 and January 1998, 131 patients of reproductive age, with anamnesis of infertility, underwent myomectomy because of the presence of at least one large myoma (diameter greater than or = 5 cm). Patients were randomly selected for treatment by laparotomy (n = 65) or laparoscopy (n = 66). The two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
218
2
36

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(269 citation statements)
references
References 24 publications
13
218
2
36
Order By: Relevance
“…Laparoscopic removal of the large fibroid using the electromechanical technique 38 makes the procedure less demanding and time consuming. Indeed, our data show a shorter mean operative time than those reported by other authors 8,10 in the presence of fibroids penetrating the uterine cavity, and may be comparable to abdominal myomectomy 39 .…”
Section: Discussionsupporting
confidence: 76%
“…Laparoscopic removal of the large fibroid using the electromechanical technique 38 makes the procedure less demanding and time consuming. Indeed, our data show a shorter mean operative time than those reported by other authors 8,10 in the presence of fibroids penetrating the uterine cavity, and may be comparable to abdominal myomectomy 39 .…”
Section: Discussionsupporting
confidence: 76%
“…In most cases of red degeneration, ultrasound findings reveal cystic spaces in the myomas. 11 Although medical therapy -including analgesics, fluids and antibiotics may be used in the majority of these patients. In patients with severe abdominal pain or an increase in myoma size causing abdominal pain and discomfort, a timely and well-planned myomectomy should be an option.…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies suggest that laparoscopic myomectomy can be a good alternative method to laparotomy for the treatment of myomas. Seracchioli et al [8,9] reported less morbidity and faster recovery in the laparoscopy group in a randomized trial that compared the results of myomectomy performed using laparotomy and laparoscopy. The incidences of miscarriage, preterm labor, and uterine rupture were similar for laparoscopic myomectomy in several studies.…”
Section: Discussionmentioning
confidence: 99%